Prinsip-Prinsip Komunikasi dalam Perspektif Al-Qur'an - Istikomah (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
The principle of communication actually has a strong scientific foundation, because it comes from the Qur'an. Through the Qur'an, humans are actually invited to communicate. Every human being needs to communicate with other people. This is done as part of human nature that cannot live alone. Indeed, not everyone can be a good and reliable communicator. There are communication techniques that must be learned if you want to be accepted from various social circles. In the Qur'an, at least six types of speech or speech styles (qaulan) are found which are categorized as rules, principles, or communication ethics, namely 1) qaulan bal??ghan; 2) qaulan mais??ran; 3) qaulan kar????man: 4) qaulan ma???r??fan; 5) qaulan layyinan; dan 6) qaulan sad??dan.